RESEARCH ON LOAD DISTRIBUTION AND FATIGUE LIFE OF FLEXIBLE BEARINGS IN HARMONIC DRIVE AFTER ASSEMBLY DEFORMATION - PAN XueJiao; DONG ShaoJiang; MU ShuFeng; ZHAO XingXin (Jixie qiangdu)
The flexible bearing is one of the key components of wave generator（ WG） in Harmonic Drive（ HD）. Its load and life studies are key to the reliable operation of HD. The flexible bearing has a significant flexural deformation of the ferrule after assembly which is different from the cam profile. Assumed that the amount of deformation of the inner ring is unknown. A set of deformation coordination equations was established. The load distribution of flexible bearings was studied. Furthermore,the fatigue life was calculated. Deformation characteristics of the flexible bearing after assembly were analyzed by finite element method（ FEM）. The comparison of results shows that the assumption is consistent with FEM and the load distribution is consistent. The fatigue life is affected by the load. It provides a reference for load analysis and fatigue life assessment of flexible bearings.